2009
DOI: 10.1161/hypertensionaha.109.130146
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Is Lower in Children and Adolescents With a Low-Saturated-Fat Diet Since Infancy

Abstract: Blood pressure was measured in the prospective randomized Special Turku Coronary Risk Factor Intervention Project Study with an oscillometric method every year from 7 months to 15 years of age in 540 children receiving a low-saturated-fat, low-cholesterol diet and in 522 control children. Dietary intakes, family history of parental hypertension, and grandparental vascular disease were recorded. Systolic and diastolic blood pressures were 1.0 mm Hg lower (95% CI for systolic: -1.7 to -0.2 mm Hg; 95% CI for dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 33 publications
3
69
1
3
Order By: Relevance
“…Consumption of >1 servings of dairy products/day and >2 servings of fruits and vegetables/day throughout adolescence has shown to lead to about a 35% lower risk of elevated BP (202). Likewise, saturated fat-reduced diet since infancy decreases BP (203). Higher sugar sweetened beverage consumption is associated with higher SBP in adolescents (204).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 99%
“…Consumption of >1 servings of dairy products/day and >2 servings of fruits and vegetables/day throughout adolescence has shown to lead to about a 35% lower risk of elevated BP (202). Likewise, saturated fat-reduced diet since infancy decreases BP (203). Higher sugar sweetened beverage consumption is associated with higher SBP in adolescents (204).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 99%
“…Salt restriction during the first year of life was found to have a significant protective effect on the BP rise in childhood, 36 as did a low saturated fat diet from age 13 months to 15 years. 37 These studies suggest that nutrition during early childhood may have a central role in the programming of future BP. Whether tracking of dietary intake from early childhood has a role is unclear, but our study found little evidence of tracking from age 18 months to mid-childhood.…”
Section: Discussionmentioning
confidence: 98%
“…29 Furthermore, we recently reported that the dietary counseling associated with better ideal cardiovascular health score, a cluster of health metrics defined by American Heart Association, which for one was favorably associated with aortic distensibility. 11 In this analysis, however, the effect of dietary counseling was not reflected on arterial distensibility.…”
Section: Discussionmentioning
confidence: 99%